2016
DOI: 10.2147/ott.s122241
|View full text |Cite
|
Sign up to set email alerts
|

Non-secretory multiple myeloma: from biology to clinical management

Abstract: Multiple myeloma (MM) is the second most common hematologic malignancy in the US. It is typically characterized by production of large amounts of defective immunoglobulin (Ig). Diagnosing MM and monitoring treatment response, including eventual relapse, are largely based on sequential measurements of Ig. However, a small subset of MM called non-secretory multiple myeloma (NSMM) produces no detectable Ig. This subset of true NSMM has become even smaller over time, as the advent of the serum free light chain ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 42 publications
0
54
1
3
Order By: Relevance
“…4) They demonstrated that time to progression, progressionfree survival, and overall survival prior to 2001 were similar between NSMM patients and secretory MM patients. 4) Between 2001 and 2012, the time frame during which new therapeutics were broadly introduced, there was a marked increase of overall survival in both groups. 4) However, the improvement in overall survival was greater in the NSMM group.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…4) They demonstrated that time to progression, progressionfree survival, and overall survival prior to 2001 were similar between NSMM patients and secretory MM patients. 4) Between 2001 and 2012, the time frame during which new therapeutics were broadly introduced, there was a marked increase of overall survival in both groups. 4) However, the improvement in overall survival was greater in the NSMM group.…”
Section: Discussionmentioning
confidence: 98%
“…4,5) The definition of MM from the 2014 International Myeloma Working Group includes 10% or more clonal plasma cells in the bone marrow or biopsy-proven bony or extramedullary plasmacytoma and one or more of the seven listed criteria (hypercalcemia, renal insufficiency, anemia, bone lesions, clonal bone marrow plasma cells ≥60%, involved/uninvolved SFLC ratio ≥100 and involved SFLC concentration ≥10 mg/dL, and 2 or more focal lesions based on MRI studies of the skeleton). 6) The International Myeloma Working Group still defines NSMM as MM lacking monoclonal protein on serum or urine electrophoresis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are MM variants or related plasma cell diseases with measurable intracellular immunoglobulin by immunofluorescence, whereas they are not measurable extracellular components via typical testing. It has been suggested that these immunoglobulins are secreted in vesicles via budding of the cell membrane, rendering them undetectable in the serum [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, in MM, the antibodies are defective and completely nonfunctional (Gerecke et al, ; Ramsenthaler et al, ; Zhang et al, ). There are also rare forms of nonsecretory MM cells that produce only light chains of Igs (Dupuis & Tuchman, ). The hallmarks of MM are primarily end‐organ damage and the occurrence of bone lesions.…”
Section: Multiple Myelomamentioning
confidence: 99%